Storyboard Development for Geospatial e-Tourism Based Augmented Reality - Johan Reimon Batmetan; Trudi Komansilan; Sondy Kumajas; Hiskia Kamang Manggopa (JR Education, 2022)
One of the important factors in designing an e-tourism based on the mobile application is the ease of use. Some of the problems often encountered by e-tourism users include the complex nature of the application, making it difficult for users to navigate. To answer user needs related to the ease of display on the application, it is necessary to design a good interface using tools and methods that are fast but effective and efficient. In the initial cycle of user interface design, a storyboard is needed as an initial description of the display that will be made. The storyboard is used as a visualization of ideas so that it can provide an overview of the appearance of the application that will be made. The storyboard makes production performance easier and eliminates trial and error. In developing this geospatial augmented reality, mobile application storyboard, we use the design sprint method. This method is widely used in start-up environments to develop software interfaces and product innovation in the consumer area. This method consists of the stages of understand, define, sketch, decide, prototype and evaluate. The use of the design method has a fast process but still provides optimal results. The results of this study indicate that the development of mobile applications using the design sprint method is able to reduce the time and energy which is relatively longer when using other methods. We conclude that storyboards can make it easier for developers to realize initial sketches into application prototypes that are high fidelity or close to the final appearance.